Enhancing mucoadhesive properties of chitosan with methacryloyl and crotonoyl groups - Shiva Vanukuru; Vitaliy Khutoryanskiy; Hisham Al-Obaidi (University of Huddersfield Press, 2023)
Nasal drug delivery holds promise for targeted administration to the brain. Mucoadhesive polymers are crucial for prolonging drug retention in the nasal mucosa. This study focuses on synthesizing and characterizing novel derivatives by reacting chitosan with crotonic and methacrylic anhydrides. The structure of the resulting derivatives was confirmed through 1H NMR and FTIR spectroscopies, while turbidity measurements revealed pH-dependent solubility profiles. Spray-drying chitosan solutions with sodium fluorescein enabled flow-through studies and texture analysis, demonstrating improved retention on sheep nasal mucosa. The findings emphasize the potential of tailored chitosan modifications for enhancing nasal drug delivery.